Comparison of empagliflozin and vildagliptin for efficacy and safety in type 2 diabetes mellitus in the Pakistani population - Khan, Asima; Khan, Izhan A.; Abidi, Hussain; Ahmed, Mansoor (Frontiers in Endocrinology, 2022)
Background Diabetes mellitus (DM) is a chronic disease that needs early management to prevent complications and premature mortality. Therefore, it is essential to select evidence-based drugs available to control diabetes and limit the progression to related complications. This study aimed to compare the efficacy and safety of empagliflozin and vildagliptin in people with type 2 DM. Methods This was an open-label, parallel randomized controlled trial (NCT 05359432) conducted at two tertiary care hospitals in Karachi, Pakistan. After obtaining consent, participants were randomized into two groups. The first group was given empagliflozin (10 mg once or two times daily) with metformin, and the second group got vildagliptin (50 mg once or two times daily) with metformin. HbA1c, high-density lipoprotein (HDL) levels, systolic blood pressure, fasting blood glucose, and body weight were measured at the baseline and 24-week visits. Results A total of 120 patients fulfilled the selection criteria and then underwent randomization to be placed into empagliflozin and vildagliptin groups. The mean change in HbA1c (-0.97% ± 0.68 for empagliflozin and -0.82% ± 1.57 for vildagliptin) was statistically similar in both groups (p-value = 0.980). No statistically significant difference was observed between the two groups for safety parameters such as eGFR (p = 0.46), serum ALT (p = 0.13), LDL (p = 0.23), total cholesterol (p = 0.49), and triglycerides (p = 0.49). Conclusion Results of the study highlight that vildagliptin and empagliflozin have a significant beneficial effect in reducing HbA1c, fasting blood glucose, systolic blood pressure, and weight of participants. Both drugs had no differences when compared on safety parameters.